ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH SEASONED EQUITY OFFERINGS - Jannah, Ika Miftahul; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze the financial statement before and after seasoned equity offerings based on the ratios i.e.: debt to equity, return on asset, return on equity and net profit margin in the companies which are listed in Indonesia Stock Exchange. The samples all companies which are listed in Indonesia Stock Exchange from 2010 to 2014, in which in 2012 added shares are offered. The sample collection by using purposive sampling method. The data analysis technique by using paired sample t-test. Based on the result of normality test, shows that the data has been distributed normally since the value of Asymp. Sig (2-tailed) < 0.05 and it is feasible to be used for further analysis. The result by using paired sample t-test, there are three significant difference i.e. return on asset, return on equity and net profit margin. These three performances of the companies experience significant changes after seasoned equity offerings in which the enhancement of sales, total assets, net profit after tax and equity after seasoned equity offerings occur. It has been found one financial performance which does not have any significant difference that is debt to equity ratio.Keywords: Financial Statement, Financial Performance, Financial Ratio, SEO